Feasibility of a Mindfulness Intervention Program in Cancer Patients in Peru: a Randomized Pilot Study - Moscoso , Manolete S. (2020)
DOI: 10.26439/persona2020.n023(1).4832 The purpose of the study was to evaluate the feasibility of a program of mindfulness intervention applied to cancer patients in the city of Arequipa, Peru. Participants were randomly selected for a six-week program or for the control group. We used psychometric instruments to measure stress and depression. Adherence and participations of the patients in the program demonstrate the feasibility of the program with breast cancer in Peru. Results show that, in comparison with the control group, there was significant reductions of perceived stress and depression amongst participants.